Factors of career development opportunities associated with organizational commitment in the hotel industry in Kuching, Sarawak - Jerry, Clarence (1999)
This study was conducted to investigate the relationship between the organizational commitment of employees in the hotel industry of Kuching, Sarawak, and the factors of career development opportunity, and also the demographic variables. The factors of career development opportunities examined in this study were job fit, job rotation, effective training and development programs, effectiveness of top management support, mentoring system, and recognition level. This study was carried out in 12 major hotels in Kuching City. A total of 364 lower and middle management level hotel employees, from the Food and Beverage Department, Front Office Department and the Housekeeping Department were selected as samples in this study.